The overconfidence effect of management and systematic risk on investors' perceptions - Alireza Kalhor; Hoda Hemmati (New Applied Studies in Management, Economics & Accounting, 2019)
The purpose of this study is to investigate the effect of management mistrust and systematic risk on investors' perceptions. The method of the present study was empirical in terms of purpose and regression analysis in terms of method. The statistical population of this study includes all companies listed on the Tehran Stock Exchange, and screening method was used to select the sample. The sample of 118 companies listed on the Tehran Stock Exchange during the period between 2012 and 2017 were considered in this study. The data required to test the research hypotheses were extracted from the annual financial statements of companies (Codal site) and the website of the Stock Exchange Organization. Relevant hypotheses were tested by multivariate panel regression method. The results showed that management overconfidence has a positive and significant effect on investors' perceptions. The results also showed a positive and significant relationship between systematic risk and investor perception.